The isolation of pathogenic fungi from seed of tropical pasture legume species - Wan Nik, Wan Zainun; Parbery, D. G. (Malaysian Society of Applied Biology, 1978)
The fungal microflora of seed of 26 species in 13 genera of tropical pasture legumes species were examined. A variety of techniques for isolating fungi have been tested and evaluated to find the most effective for isolating pathogenic, saprophytic and storage fungi. Numerous fungi were isolated from seeds placed on blotter and on potato dextrose agar. Many Fusarium species were isolated on Nash-Snyder agar , while storage fungi were Isolated mostly on salt- malt agar. A total of 42 species of-fungi in 20 different genera were isolated.